Language Needs of Malaysian Public Relations Undergraduates in ESL Writing - Low Shun Jun; Paul GnanaSelvam Pakirnathan; Mariann Edwina (The English Teacher, 2020)
In recent years, it has become increasingly evident that Public Relations (PR) undergraduates are not competent in ESL writing even though communicating through writing is an important skill in the PR industry. This study aims at accessing the ESL writing performance and exploring language challenges and needs of Malaysian PR students. Using the embedded mixed methods research design, 45 Malaysian PR undergraduates were selected through a purposive sampling. Data were collected through students’ speech writing samples and semi-structured interviews. Students’ writing performances were descriptively measured using SPSS while textual and thematic analyses were conducted to explore the types of errors and students and teachers’ feedback on their writing experiences. This study found that the majority of the students scored average grades (M=52.37) in their writing exercises. The main concerns for language needs included subject-verb agreement, syntax error, tenses, language used, preposition, mechanics, semantics, conjunction, dangling modifiers and verb consistency. It was also found that the difficulties faced by the PR students in writing were not only caused by their language needs, but the lack in generating critical and matured content. This study is significant in informing undergraduates and English language Teachers (ELT) who are teaching the PR programs at Malaysian universities and the PR industry in general.